2023
DOI: 10.3389/fonc.2023.1210381
|View full text |Cite
|
Sign up to set email alerts
|

HPV infection and breast cancer risk: insights from a nationwide population study in Taiwan

Abstract: BackgroundThe prevalence of cancer, specifically breast cancer, has raised globally. The etiology of breast cancer has been attributed to age, genetic mutations, reproductive history, hormone therapy, lifestyle factors, and viral infections. The human papillomavirus (HPV) has been one of the most widespread sexually transmitted infection in the United States. The role of HPV in breast oncogenesis was hypothesized before, yet the association remained unclear.MethodsIn this study, we employed a nationwide popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The potential mechanisms by which HPV may contribute to the development of BC are not yet fully understood. It is hypothesized that HPV infection may activate oncogenic pathways, induce immune dysfunction, or directly integrate viral DNA into the host genome, leading to BC development (33)(34)(35). However, more research is needed to clarify the underlying mechanisms and establish a definitive link between HPV and BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential mechanisms by which HPV may contribute to the development of BC are not yet fully understood. It is hypothesized that HPV infection may activate oncogenic pathways, induce immune dysfunction, or directly integrate viral DNA into the host genome, leading to BC development (33)(34)(35). However, more research is needed to clarify the underlying mechanisms and establish a definitive link between HPV and BC.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have failed to find a consistent association between HPV and BC (32). The potential mechanisms of HPV-mediated cancer development have not yet been proven, but it is hypothesized that HPV infection may cause BC through activation of oncogenic pathways, immune dysregulation, or direct integration of viral DNA into the host genome (33)(34)(35). In addition, HPV infection may interact with other risk factors, such as hormonal imbalance or genetic predisposition, to increase the risk of BC (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of HPV in malignant breast tumors has been reported, indicating a potential role of HPV in the early stage of breast cancer and breast carcinogenesis [7][8][9][10][11]. The existence of a causal link between HPV infection and breast cancer is still subject to debate; while some research revealed a higher risk consistent with a possible role of HPV in the development of breast cancer [5,8,10,[12][13][14][15][16][17][18], other studies found no such association [19][20][21][22][23][24]. Data, however, is limited in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…While HPV is primarily linked to these mucosal cancers, its association with skin cancers is less direct but increasingly studied [ 2 , 3 ]. HPV infections are generally asymptomatic, with warts being the most common clinical manifestation on the skin [ 4 , 5 ]. Although 90% of HPV infections will clear up on their own within two years, the risk of developing cancer increases with prolonged latency and frequent infections [ 5 ].…”
Section: Introductionmentioning
confidence: 99%